Mathematics illustrated dictionary facts, figures, and people including the new math - Bendick, Jeanne (McGraw-Hill, 1965)
Over 150 entries define mathematical principles, terms, symbols, and abbreviations, and present short profiles of work of famous mathematicians. An appendix includes tables of mathematical symbols, formulas, weights and measures, and square roots, and logarithms.